Barriers to Sustainable Practices towards Low Carbon Emission Projects in Malaysia - M. A. Klufallah, Mustafa; Othman, Idris; Fadhil Nuruddin, Muhd; Faris Khamidi, Mohd (International Journal of Engineering and Technology, 2018)
The Malaysian construction  industry  significantly  contributes   as an empowerment to its development  vision  of  2020  by  reducing up to 40% of carbon emission. Moreover, the industry accounts as threat to the environment, not  only  in  terms  of natural  resources  consumption but  also  in emitting million tons of carbon emission annually. In fact, Malaysia is categorized the 30th in  the  world’s  ranking  in  carbon  emission  level. Several studies attempt to investigate and review barriers that face construction stakeholders in order to provide integration of sustainability in construction industry. However, the barriers were lacking in terms of addressing carbon emission aspects of sustainable practice and limit the emissions from construction projects in Malaysia. This paper investigates the major barriers of organization in achieving sustainability’s best practice. The identified barriers from the perspective of construction stakeholders in Malaysia were categorised based on factor analysis, which are professional and capacity, design and technologies, cost and finance, and, knowledge and culture.